Levels, sources, variations, and human health risk assessment of 90Sr and 137Cs in water and food around Sanmen Nuclear Power Plant (China) from 2011 to 2020 - Wang, Peng; Yu, Shunfei; Zou, Hua; Lou, Xiaoming; Ren, Hong; Zhou, Lei; Lai, Zhongjun; Xuan, Zhiqiang; Gao, Xiangjing; Xu, Qiuliang; Zhou, Zhen; Zhao, Yaoxian; et al. (Frontiers in Public Health, 2023)
Objectives: Radioactivity monitoring around nuclear facilities is crucial to provide important baseline data for effective detection of radioactive leakage to the environment. We aim to establish a baseline study for monitoring radioactive levels of 90Sr and 137Cs around Sammen Nuclear Power Plant (SNPP) and to assess their associated health impact on surrounding residents. Methods: In this study, we collected water and food samples around the SNPP from 2011 to 2020 and determined for 90Sr and 137Cs activity concentrations. We statistically analyzed the temporal trends of 90Sr and 137Cs and evaluated their radiation exposure to the local residents. Results: During this period, the activity concentrations of 90Sr and 137Cs varied within 1.2 - 9.9 mBq/L and 0.10 - 7.6 mBq/L in water, and 0.037 - 1.3 Bq/kg and 0.011 - 0.45 Bq/kg in food, respectively, with no significant seasonal variation trend. Conclusions: All reported activity concentrations of 90Sr and 137Cs were significantly lower than the recommended value of WHO and Chinese national standards. There is no indication of notable radioactive release into the study area due to the operation of SNPP during 2018-2020. The annual effective doses (AEDs) from the ingestion of 90Sr and 137Cs in water and food were well below the international permissible limits, indicating the radiation exposure around SNPP during 2011-2020 was kept at a safe level.